Multidimensional Scaling dan K-Means Clustering Kabupaten/Kota di Nusa Tenggara Timur Berdasarkan Tujuan Pembangunan Berkelanjutan - Yuliana Kurniawati Dima; Fadel Muhammad (Jurnal Statistika Terapan (ISSN 2807-6214), 2024)
The Sustainable Development Goals agreed on 17 goals to be achieved by 2030. The Indonesian government has set 7 of the 17 prioritized goals including ending poverty, zero hunger, healthy and prosperous lives, gender equality, marine ecosystems, partnerships to achieve goals and industry, innovation and infrastructure. East Nusa Tenggara is one of the provinces with the highest poverty rate, low education level, high infant/toddler mortality rate, and low access to proper sanitation. This research aims to group districts/cities in NTT using multidimensional scaling and k-means clustering based on sustainable development goals including poverty, education, health and proper sanitation. The result is three groups with poor, moderate and good quality of life. The government needs to formulate comprehensive and sustainable strategies/policies to improve people's living standards, especially in districts with high poverty, low education, low health quality and lack of access to proper sanitation.